THU0211 Gastrointestinal manifestations of behçet's disease in japan: A study of 43 patients. (23rd January 2014) - Ideguchi, H.; Suda, A.; Takeno, M.; Ohno, S.; Ishigatsubo, Y.
Abstract : Objectives: We analyzed the clinical gastrointestinal (GI) characteristics of Behçet's disease (BD) patients in Japan. Methods: We retrospectively reviewed the clinical charts of 412 patients who fulfilled the 1987 Japanese criteria for BD and were treated in two University hospitals from July 1991 to December 2007. Results: Forty-three patients (10.4%) had BD related GI lesions which were shown by imaging examinations. Mean age at BD diagnosis and onset of GI episodes were 34.2 and 36.2 years, respectively. The patients suffered from abdominal pain (70%) and GI bleeding (42%), while they had lower frequency of eye involvement and higher incidence of arthritis and vascular involvement than BD patients without GI lesions. The lesions were prevalent in the ileum (74%) followed by cecum (49%) and esophagus (21%). The patients were treated with mesalazine and sulfasalazine (96%), corticosteroids (74%), immunosuppressants (30%), and infliximab for 7 patients having refractory lesions (16%), while 10 patients had surgical operation (23%). Two patients died due to non-GI events during the observation. Conclusions: The diagnosis of BD was often difficult because of lack of eye involvement. Surgery is required for some patients in spite of intensive immunosuppressive therapies. Appropriate use of anti-TNF agents may be promising for the GI involvement. Disclosure of Interest: None Declared